SMART SAFETY HELMET: PENDETEKSI KARBON MONOKSIDA (CO) DI LOKASI PENGGALIAN SUMUR DAN PERTAMBANGAN - Darwanto, Agus; Elin, Elyne Kusuma Mahardika; Nasywa, Nasywa Athaya Hermawan; Rohadatul Nur Afifah (Jurnal Inovasi Daerah, 2024)
The well excavation or drainage process often results in casualties due to the presence of poison gas at the bottom of the well. Workplace accidents caused by toxic gases in mining locations also frequently loss of life. This research aims to create a smart safety helmet, a project helmet for personal protection equipped with an MQ-2 sensor to detect toxic gases, connected to a smartphone application using IoT (Internet of Things) technology. Data collection involves calibration tests and simulation tests. Data analysis employs descriptive statistical analysis in the form of numbers and tables. The creation of the smart safety helmet involves integrating Arduino devices with an MQ-2 sensor, LCD, buzzer, power bank, and IoT technology connected to the mobile phones of operators or project supervisors. This integration enables the helmet to detect and relay information about CO gas and its safety status. Based on the performance test results and calibration tests using Automotive Diagnostic Solutions owned by the Cilacap District Transportation Agency, the smart safety helmet has been proven effective in detecting the presence of carbon monoxide by being worn by mining workers and well diggers, thus detecting CO levels and its safety status. If the CO level reaches 1500 ppm or more, the operator or project manager can immediately prepare rescue measures.